1970
DOI: 10.2514/3.5834
|View full text |Cite
|
Sign up to set email alerts
|

Thin-wire Langmuir-probe measurements in the transition and free-molecular flow regimes

Abstract: idea of the range of applicability of Cohen's solution, the percentage error in / + [from his Eq. (19)] as a function of r P * for constant values of K is given in Fig. 8.Cicerone and Bowhill obtain numerical solutions for the attracted ion distribution at large probe potential and the corresponding probe characteristics. The characteristics presented, covering a range of .1 < p p < I and an approximate potential range of 20 < & p * < 500, agree with the current results in the overlapping potential range, at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1971
1971
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Therefore we concentrated on the effect of collisions on positive-ion collection by a Langmuir probe. This effect has already been studied extensively; examples of earlier papers on this subject are [13][14][15][16][17][18][19][20][21][22]. Qualitatively speaking the effect of collisions on the positive-ion collection is demonstrated in two ways:…”
Section: The Influence Of Ion-neutral Collisions On Probe Measurementsmentioning
confidence: 99%
“…Therefore we concentrated on the effect of collisions on positive-ion collection by a Langmuir probe. This effect has already been studied extensively; examples of earlier papers on this subject are [13][14][15][16][17][18][19][20][21][22]. Qualitatively speaking the effect of collisions on the positive-ion collection is demonstrated in two ways:…”
Section: The Influence Of Ion-neutral Collisions On Probe Measurementsmentioning
confidence: 99%
“…5 in Ref. 16 and Fig. 9 in this paper shows an essential resemblance in the variation of the ion current at r p /l D < 1.…”
Section: Probe Response In the Oml Regionmentioning
confidence: 60%
“…On the other hand, the reported results differ between themselves in some respects. 1 ' 11 ' 14 ' 16 It is suggested that at least part of the apparent disagreement can be explained in terms of ion-neutral collisional effects described in this paper.…”
Section: Probe Response In the Oml Regionmentioning
confidence: 80%
See 1 more Smart Citation
“…and the probe length / was 0.4 in., affording an l/D ratio of 100. Previous studies 25 have demonstrated no dependence on the derived electron temperature or number density on the fineness ratio, I/D at l/D values down to 50.…”
Section: Details Of the Measurementsmentioning
confidence: 95%